Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I take a $U(x,y)$ on $\mathbb{R}^2$, then a fixed $P_0=(x_0,y_0)$ where $U_x(P_0)=U_y(P_0)=0$.

Can I automatically say that $U_{xx}(P_0)=U_{xy}(P_0)=U_{yy}(P_0)=0$ (without calculating before $U_{xx}$, $U_{xy}$, $U_{yy}$ and then evaluating them on $P_0$)?

Thanks a lot.

share|cite|improve this question
up vote 3 down vote accepted

No. You should differentiate for the second time before evaluation, and the result of evaluation may well be nonzero. For a concrete example take $U(x,y)=x^2+xy+y^2 $ at $P=0$. All first order derivatives vanish at P, but the second order derivatives are nonzero.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.